Pengaruh Non Performing Financing, Beban Operasional Pendapatan Operasional, dan Ukuran Perusahaan Terhadap Bank Pembiayaan Rakyat Syariah di Indonesia - Annisa Fitri Anugrah Sari; Achmad Fauzi; Dwi Kismayanti Respati (Econosains Jurnal Online Ekonomi dan Pendidikan, 2022)
This study aims to determine the effect of Non-Performing Financing, Operating Expenses, Operating Income, and Company Size on the Profitability of Islamic Rural Banks in Indonesia. The data collection technique used is the library data source by collecting data using documentation techniques. The affordable population in this study is the Islamic Rural Banks (BPRS), registered with the Financial Services Authority (OJK) in 2018 - 2020 with a total of 144 banks. Data is obtained from the BPRS annual financial report on the OJK website. The sample used was 102 BPRS using the random sampling technique and the Isaac and Michael formula. The results of this study indicate that the NPF has a significant negative effect on profitability because the higher the NPF value, the lower the profitability. Then, the BOPO significantly negatively affects profitability because the higher the BOPO value, the lower the profitability. The company's size does not affect profitability because the more total assets owned, the more costs needed so that profitability decreases. NPF, BOPO, and company size have a significant positive effect on profitability because the higher the value of these three variables, the higher the profitability. The coefficient of determination describes the ability of NPF, BOPO, and company size that affect profitability by 22.8%, while the rest is influenced by other factors that have not been studied.